Natures instead of nature—plural perceptions and representations of nature and its challenges for ecological transition: a systematic review of the scientific production - Vidal, Diogo Guedes; Alves, Fátima; Valentim, Cristina Sá; Freitas, Helena (Environmental sciences Europe, 2024)
Background Recognizing nature and the environment as sociocultural constructions is critical to enhancing a transformational ecological change. This involves understanding their diverse sociocultural meanings and societal approaches and how these understandings affect equitable ecological transitions. We reviewed empirical studies and essays, categorizing 161 studies into three main categories: opposition, domination, and interdependencies, reflecting varying knowledge, power dynamics, cultures, and contexts. These studies aim to uncover how societies conceptualize, explain, and engage with nature and the environment, shaping society–nature relationships and influencing ecological transitions. Results This study underscores the diverse perceptions and representations of nature, from a controllable resource to an integrated web of life. Three main categories emerged: (i) nature against society, in a logic of opposition; (ii) nature subordinated to society, in a logic of domination, although integrated into society; and (iii) nature united with society, in a logic of interdependence. Thus, this study advocates discussing “natures” as sociocultural constructs, highlighting the plurality of social perceptions and representations, which can inform policies and challenge socio-political and socio-economic systems. Conclusions This review may pave the way to, first, give visibility and value that diversity and plurality as an instrument that can enrich policies and defy socio-political and socio-economic systems to change and, second, identify the main drivers and resistances that the implementation of an ecological transformation change may face in different sociocultural contexts.